HUBUNGAN INDEKS MASSA TUBUH DENGAN USIA MENARCHE PADA REMAJA PUTRI DI KECAMATAN TIGO NAGARI KABUPATEN PASAMAN - Lita Angelina Saputri; Lisa Rahmawati; Yulfa Henim Rumita (Universitas Pahlawan Tuanku Tambusai, 2021)
On the last decades, age at menarche has significantly decreased with average 8-9 days each year. This condition may effect on health status such as breast cancer, ovarium cancer, cardiovaskuler disease and tipe 2 diabetes mellitus. The objective of this study was to determine the relationship between BMI with age at menarche. This was an observational analitycal study withÂ cross sectional design. The study was conducted on August 2019 â€“ April 2020 in elementry and junior high school in Tigo Nagari, Pasaman West Sumatera. The population was all girls aged 9-15 years with maximum first menstrual period less than four month ago. The sample of this study was chosen with quota sampling about 96 respondents. Data were analyzed by unvariate and bivariate using chi square test with computerization. The result showed about 29,9% respondents with abnormal BMI and 45,8%. respondents with abnormal age at menarche. There was a relationship between BMI with age at menarche with p value = 0,035 (p<0,05). It is expected to the health workers and the school can provide counseling and education about the importance of BMI monitoring in adolescence.